The Flexural Behavior of One-Way Concrete Bubbled Slabs Reinforced by GFRP-Bars with Embedded Steel I-Sections - Abdulkhaliq, Mohannad; Al-Ahmed, Ali Hussein (Engineering, Technology & Applied Science Research, 2024)
This study examines the behavior of polymer bubbled deck slab systems, one-way concrete slabs with polymer sphere voids reinforced with Glass Fiber-Reinforced Polymer (GFRP) rebars, and embedded I-shaped steel beams. Six one-way structural concrete slabs (2600 mm long, 600 mm wide, 150 mm deep) were tested and directly supported under two points bending. Five Bubbled Slabs (BS), one of which was un-strengthened, were compared to the reference Solid Slab (SS) without polymer spheres. Each slab had 95 polymer sphere voids of 90 mm diameter and 15.48% self-weight decrease. Several parameters, including specimen type (SS or BS) and internal strengthening, were optimized using steel I-shapes in two distinct forms (2 and 4 pcs. of steel I-sections). Channel Shear Connectors (CSCs) and bent-up steel bars (10 mm in diameter) were implemented to increase shear resistance, with the 4I-section form having a cross-sectional area equivalent to the 2I-section form. In contrast to the SS, the BS exhibited a wider range of deformations during the same loading stage, with ultimate load capacity decreasing by 30% and deflection occurring at a greater ratio of approximately 18% to 85%. Additionally, the embedded steel I-shapes improved specimen performance compared to BS and SS. This occurred by reducing deflection at a service load by 60% and 49%, eliminating cracks, improving ultimate load capacity by 85% and 30%, and enhancing flexural stiffness by 102% and 71%, respectively, at the ultimate loading stage. CSC increased ultimate load by 13% to 22% and deflection by 8% to 15%, compared to specimens without CSC.